2016
DOI: 10.1016/j.jvir.2015.12.751
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Repeat Administration of Adventitial Delivery of Lentivirus-shRNA-Vegf-A in Arteriovenous Fistula to Prevent Venous Stenosis Formation

Abstract: Purpose Previous study has demonstrated that adventitial delivery of lentivirus mediated Vegf-A shRNA (LV-shRNA-Vegf-A, small hairpin RNA that inhibits Vegf-A gene expression) at the time of arteriovenous fistula (AVF) creation increases the lumen vessel area (LVA) of the outflow vein and reduces venous neointimal hyperplasia (VNH). However, the effect of decreasing Vegf-A and improving LVA decreases by 2-weeks as stenosis develops. The aim of the present study was to determine if a second dose of LV-shRNA-Veg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 28 publications
(50 reference statements)
2
17
0
Order By: Relevance
“…Mice were anesthetized with a ketamine (100 mg/kg body weight) and xylazine (10 mg/kg body weight) mixture prior to surgery, and nephrectomy was performed to create CKD as described. 10 , 17 , 22 , 23 , 24 The mice undergoing this procedure have been shown to have elevated BUN and creatinine by 3–4 weeks after nephrectomy. 10 , 17 , 22 , 23 , 24 After 28 days of CKD creation, the left carotid artery was connected to the left jugular vein to create an AVF as described.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Mice were anesthetized with a ketamine (100 mg/kg body weight) and xylazine (10 mg/kg body weight) mixture prior to surgery, and nephrectomy was performed to create CKD as described. 10 , 17 , 22 , 23 , 24 The mice undergoing this procedure have been shown to have elevated BUN and creatinine by 3–4 weeks after nephrectomy. 10 , 17 , 22 , 23 , 24 After 28 days of CKD creation, the left carotid artery was connected to the left jugular vein to create an AVF as described.…”
Section: Methodsmentioning
confidence: 99%
“… 10 , 17 , 22 , 23 , 24 The mice undergoing this procedure have been shown to have elevated BUN and creatinine by 3–4 weeks after nephrectomy. 10 , 17 , 22 , 23 , 24 After 28 days of CKD creation, the left carotid artery was connected to the left jugular vein to create an AVF as described. 22 The outflow vein of the fistula, also referred to as the GV, and the contralateral jugular vein (CV) of the same mouse as the control vein were excised for PCR at days 3 and 7 of fistula creation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, bone marrow-derived mesenchymal stem cells treated with VEGF differentiate into endothelial-like cells and significantly attenuate neointimal thickness [ 84 ]. However, lentivirus-mediated VEGF-A inhibition can decrease the venous neointimal hyperplasia of AVFs [ 85 ]. This evidence suggested that the effect of VEGF on neointimal formation is complicated.…”
Section: Endothelial Cell Secretory Functionmentioning
confidence: 99%